Growth differentiation factor-15/adiponectin ratio as a potential biomarker for metabolic syndrome in Han Chinese - Zheng, Shuai; Shen, Min; Qian, Yu; Li, Shushu; Chen, Yang; Jiang, Hemin; Lv, Hui; Chen, Doudou; Zhao, Ruiling; Zheng, Xuqin; Sun, Min; Yang, Tao; et al. (Frontiers in Endocrinology, 2023)
Aims: Growth differentiation factor-15 (GDF-15) and adiponectin are adipokines that regulate metabolism. This study aimed to evaluate the roles of GDF-15, adiponectin, and GDF-15/adiponectin ratio (G/A ratio) as biomarkers for detecting metabolic syndrome (MS). Materials and Methods: This cross-sectional study included 676 participants aged 20–70 years in Jurong, China. The participants were divided into four groups based on sex and age (<40 and ≥40 years). MS was defined according to the modified National Cholesterol Education Program Adult Treatment Panel III criteria. Receiver operating characteristic curves were used to evaluate the performance of GDF-15, adiponectin, and the G/A ratio in predicting MS. Results: The prevalence of MS was 22.0% (149/676). Logistic regression analysis indicated that the G/A ratio and adiponectin levels, but not GDF-15 levels, were correlated with MS [odds ratio; 95% CI 1.010 (1.006–1.013) and 0.798 (0.735–0.865), respectively] after adjusting for confounding factors. The G/A ratio displayed a significant relationship with MS in each subgroup and with each MS component in both men and women; however, adiponectin concentrations were significantly associated with MS and all its components only in men (all P <0.05). The area under the curve (AUC) of the G/A ratio and the adiponectin level for MS was 0.758 and 0.748, respectively. The highest AUC was 0.757 for the adiponectin level in men and 0.724 for the G/A ratio in women. Conclusions: This study suggests that the G/A ratio and adiponectin are potential biomarkers for detecting MS in women and men, respectively.